Pengaruh Lingkungan Kerja, Asistensi Manajemen, dan Kebijakan Kompensasi Terhadap Retensi Karyawan di SMK Hang Tuah 2 Jakarta - Wullur , Susana; Wahyudin , Dian (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2025)
This research aims to analyze the influence of the work environment, management assistance, and compensation policy on employee retention at SMK Hang Tuah 2 Jakarta. Data was collected using a questionnaire that was tested for validity and reliability. The research sample consisted of 50 employees of SMK Hang Tuah 2 Jakarta, selected using a saturated sampling technique. The data analysis technique employed multiple linear regression analysis using SPSS for Windows Ver. 29. The findings of this research indicate that: (1) the work environment has a positive and significant influence of 65.8% on employee retention variation, with a significance value of 0.001, (2) management assistance has a positive and significant influence of 74.1% on employee retention variation, with a significance value of 0.006, (3) compensation policy has a positive and significant influence of 85.1% on employee retention variation, with a significance value of 0.000, and (4) simultaneously, the work environment, management assistance, and compensation policy have a positive and significant influence of 85.5% on employee retention variation, with a significance value of 0.000. These findings indicate that improving the work environment, management assistance, and compensation policy will enhance employee retention.